Operator health risk evaluation of off-highway dump truck under shovel loading condition - Shen, Yan-hua; Xu, Min; Jin, Chun; Gao, Yu; Wei, Fu-lin (Journal of Central South University, 2015)
To evaluate the operator health risk exposed to whole-body vibration (WBV) while the electric-shovel loads the ore on the truck body, the semi-truck mathematical model and 3-D virtual prototype were built to simulate the high shockwave of truck cab under the shovel loading. Discrete element method was utilized to accurately estimate the impacting force on the truck body. Based on the ISO 2631-5 criteria, the S ed is about 0.56 MPa in both models, which means that the dump operators have a high probability of adverse health effects over long-term exposure to these vibrations. The 4-DOF operator model was built to investigate the biodynamic response of seated-human body exposed to WBV in terms of the transmission of vibrations through the body. The results show that the response peak is in the frequency range of 4–6 Hz corresponding to the primary body resonant frequency.